The Optimation of Fermentation Time, Antibacterial Activity and Profiling Secondary Metabolite of Symbiont Fungi from Sponge Gelliodes fibulata - Rusmalina, Siska; Mahfur, Mahfur; Hasanah, Nunung; Wiyono, Mochamad Ardy; Ekayanti, Nonik Nur; Nathania, Jacinda Caroline (Pharmaciana, 2024)
Symbiont fungi are organisms that live in sponges tissue. Sponges are known to contain many metabolites which have the potential to be used as raw materials for medicine. Sponge Gelliodes fibulata is belongs to category demospongiae. The purpose of this study was to determine the optimal time to obtain the best secondary metabolite profile results in the sponge symbiont fungus Gelliodes fibulata. This research is included in experimental research. Beginning with the fungi culture of the sponge Gelliodes fibulata. Followed by a fermentation process with variations in time 2, 4, 6, 8, 10, 12, and 14 days to get the secondary metabolites produced. A liquid extraction process is carried out to obtain secondary metabolites produced during fermentation. The final stage is to carry out qualitative analysis with TLC and antibacterial testing with the well-diffusion method. The results obtained show that the long fermentation time influences the secondary metabolites obtained, and the metabolites possessed influence their antibacterial activity. The profile of secondary metabolites from TLC showed that the 10th day of fermentation had the most complex secondary metabolites and the highest yield 0.086%. The results of antibacterial activity showed that the 10th day of fermentation had the largest inhibition zone with 7.75 ± 0.44 mm compared to the other days of fermentation.